Positive electrode material and preparation method thereof, electrochemical device and electronic device

By adding lithium, sodium and nitrate ions to the cathode material, expanding the transmission channel of lithium ions and improving the density of the SEI film, the shortcomings in the cycle life, kinetic performance and cost of the existing ternary cathode material batteries are solved, and more efficient electrochemical performance and lower material costs are achieved.

CN119542410APending Publication Date: 2025-02-28NINGDE AMPEREX TECHNOLOGY LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510027319.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing lithium-ion batteries with ternary positive electrode materials have shortcomings in terms of cycle life, energy density, charging rate and discharge power, and the material cost is relatively high.

Method used

By adding lithium, sodium and nitrate ions to the positive electrode material and controlling their mass proportion, expanding the transmission channel of lithium ions, improving the diffusion coefficient and deintercalation quantity of lithium ions, forming a thinner and denser SEI film, improving kinetic performance and structural stability.

Benefits of technology

It improves the diffusion rate of lithium ions on the surface of the positive electrode material, improves the dynamic performance and high-temperature cycle stability of the electrochemical device, extends the cycle life of the electrochemical device, and reduces the material cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542410A_ABST
    Figure CN119542410A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode material and a preparation method thereof, an electrochemical device and an electronic device, the positive electrode material comprises a lithium element, a sodium element and nitrate ions, and based on the mass of the positive electrode material, the mass ratio of the nitrate ions is 0.001%-0.2%. The high-temperature cycling stability, the capacity utilization rate and the dynamic performance of the electrochemical device are improved, and meanwhile the impedance of the electrochemical device is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemistry, and in particular to a positive electrode material and a preparation method thereof, an electrochemical device and an electronic device. Background Art

[0002] Currently, lithium-ion batteries based on ternary cathode materials have been widely used in portable electronic devices and drones, and therefore higher requirements are placed on their performance. Specifically, it is necessary to further improve the cycle life, energy density (such as the specific capacity of the cathode material), charging rate and discharge power of the ternary cathode materials, while reducing the material cost. Summary of the invention

[0003] In view of this, the present application provides a positive electrode material and a preparation method thereof, an electrochemical device and an electronic device.

[0004] In a first aspect, the present application provides a positive electrode material, which includes lithium element, sodium element and nitrate ions. Based on the mass of the positive electrode material, the mass proportion of nitrate ions is 0.001% to 0.2%.

[0005] The present application can expand the transmission channel of lithium ions, increase the diffusion coefficient of lithium ions in the positive electrode material and the number of lithium ions that can be intercalated and deintercalated through the synergistic effect of lithium elements, sodium elements and nitrate ions, form a thinner and denser SEI film on the positive electrode surface, increase the diffusion rate of lithium ions on the surface of the positive electrode material, improve the kinetic performance (charge and discharge rate) of the electrochemical device, improve the structural stability of the positive electrode material, and enable the electrochemical device of the present application to have good high temperature (45°C and above) cycle stability performance.

[0006] Based on the first aspect, in some possible implementations, the positive electrode material further includes a boron element, and the mass proportion of the boron element is 0.02% to 0.3% based on the mass of the positive electrode material.

[0007] This application forms a dense coating on the surface of the positive electrode material by adding boron elements to the surface of the positive electrode material and controlling its mass ratio to meet the above range, thereby reducing the corrosion of the electrolyte on the surface of the positive electrode material. At the same time, it can reduce the release of oxygen on the surface of the positive electrode material and reduce the phenomenon of irreversible phase change from the surface of the positive electrode material to the bulk phase, thereby further improving the high temperature (45°C and above) cycle stability of the electrochemical device.

[0008] Based on the first aspect, in some possible embodiments, the particle size Dv50 of the positive electrode material is 2 μm to 15 μm, (Dv90-Dv10) / Dv50 is 0.5 to 1.2, Dv10 is 0.9 μm to 1.9 μm, and Dv90 is 4 μm to 7 μm.

[0009] The present application controls the particle size Dv50 of the positive electrode material to meet the above range, which helps to shorten the diffusion path of lithium ions in the positive electrode material and further improves the kinetic performance (charge and discharge rate) of the electrochemical device.

[0010] In addition, the present application also helps to improve the uniform distribution of the positive electrode material particles by controlling (Dv90-Dv10) / Dv50 to meet the above range, which helps to achieve uniform participation of the entire positive electrode material in the electrochemical reaction, thereby improving the capacity utilization of the positive electrode material and improving the overall capacity of the electrochemical device of the present application. Further, the uniform distribution of the positive electrode material particles is also conducive to reducing the uneven phenomenon during the electrochemical reaction, reducing the cracking and detachment of particles caused by stress concentration and volume change, and further improving the high temperature (45°C and above) cycle stability of the electrochemical device, and extending the cycle life of the electrochemical device. Further, the uniform distribution of the positive electrode material particles can further improve the transmission efficiency of lithium ions and reduce the internal resistance, thereby improving the kinetic performance (charge and discharge rate) of the electrochemical device, so that it can maintain a higher capacity at high rate discharge. Further, the uniform distribution of the positive electrode material particles also helps to form a dense and continuous conductive network, reduce the contact resistance between the positive electrode material particles, and thus reduce the impedance of the electrochemical device.

[0011] Based on the first aspect, in some possible embodiments, the particle size Dv50 of the positive electrode material is 3.3 μm to 10 μm, and (Dv90-Dv10) / Dv50 is 0.7 to 0.9.

[0012] The present application further improves the high temperature (45°C and above) cycle stability and kinetic performance (charge and discharge rate) of the electrochemical device and reduces the impedance of the electrochemical device by further regulating Dv50 and (Dv90-Dv10) / Dv50 to meet the above range.

[0013] Based on the first aspect, in some possible embodiments, the specific surface area BETm of the positive electrode material is 2 / g, 1≤BET≤4.

[0014] The present application controls the specific surface area of ​​the positive electrode material to meet the above range, which is conducive to providing more interfaces for the insertion and extraction of lithium ions, thereby increasing the capacity of the electrochemical device and further improving the kinetic performance (charge and discharge rate) of the electrochemical device.

[0015] The second aspect of the present application provides a method for preparing the above-mentioned positive electrode material, comprising the following steps: (1) A metal salt containing Ni, a metal salt containing Mn, and a metal salt containing Co are used as transition metal ion sources, and ammonia water is used as a coprecipitant and a complex, and the three are subjected to a coprecipitation reaction to obtain a transition metal hydroxide precursor; in the present application, the metal salt containing Ni is specifically NiSO4, the metal salt containing Mn is specifically MnSO4, and the metal salt containing Co is specifically CoSO4; (2) sintering a transition metal hydroxide precursor, Li2CO3 and Na2CO3 in an air atmosphere to obtain an intermediate; (3) treating the intermediate and a lithium-containing compound at 350° C. to 600° C. for 12 to 48 hours, and then washing and drying the intermediate and the lithium-containing compound to obtain a first material; the lithium-containing compound of the present application is specifically lithium hydroxide and lithium nitrate; (4) The first material, sodium nitrate and boron oxide are mixed and then heat treated to obtain the positive electrode material of the present application.

[0016] In the present application, a certain amount of sodium element is added. Since the radius of sodium ions is larger than that of lithium ions, after doping a certain amount of sodium ions in the lithium layer, the interlayer spacing of the lithium layer can be expanded, thereby expanding the channel in the lithium deintercalation process, thereby improving the kinetic performance (charge and discharge rate) and capacity utilization of the electrochemical device. In addition, lattice distortion can be alleviated and the stability of the bulk structure of the positive electrode material can be improved.

[0017] Based on the second aspect, in some possible embodiments, the chemical formula of the transition metal hydroxide precursor is Ni a Co c Mn b (OH)2, where 0.45≤a≤0.5, 0.45≤b≤0.5, b / a=1, 0≤c≤0.1, a+b+c=1.

[0018] The above transition metal hydroxide precursor is used to prepare the positive electrode material of the present application, so that the electrochemical device has good high temperature (45°C and above) cycle stability and kinetic performance (charge and discharge rate).

[0019] Based on the second aspect, in some possible embodiments, the transition metal hydroxide precursor is a spherical secondary particle, the secondary particle includes a first material layer and a second material layer, b / a in the first material layer is 0.83 to 0.94, and b / a in the second material layer is 1 to 1.05; The first material layer is within a range of 1 / 6R from the center of the secondary particle, where R is the shortest distance from the center of the secondary particle to the surface of the secondary particle.

[0020] In the present application, the atomic weight of the Mn element on the surface of the transition metal hydroxide precursor is controlled to be greater than the atomic weight of the Ni element. Compared with the nickel-rich surface, the manganese-rich surface is more easily reacted with lithium salts, thereby improving the reactivity of the transition metal hydroxide precursor. At the same time, the positive electrode material prepared from the above transition metal hydroxide precursor has better high temperature (45°C and above) cycle stability performance.

[0021] Based on the second aspect, in some possible embodiments, the specific surface area BETm of the transition metal hydroxide precursor is 2 / g, 9≤BET≤15.

[0022] The present application controls the specific surface area of ​​the transition metal hydroxide precursor to meet the above range, so that the transition metal hydroxide precursor has better reaction activity and also has a suitable primary particle size, thereby further improving the high temperature (45°C and above) cycle stability and kinetic performance (charge and discharge rate) of the electrochemical device and reducing the impedance of the electrochemical device.

[0023] Based on the second aspect, in some possible embodiments, the tap density of the transition metal hydroxide precursor is TDg / cm 3 , 1.7≤TD≤2.2.

[0024] The present application controls the tap density of the transition metal hydroxide precursor to meet the above-mentioned range, so that the transition metal hydroxide precursor has good compactness. The positive electrode material of the present application prepared using this transition metal hydroxide precursor has a suitable specific surface area and compactness, further improving the high temperature (45°C and above) cycle stability and kinetic performance (charge and discharge rate) of the electrochemical device and reducing the impedance of the electrochemical device.

[0025] The third aspect of the present application provides an electrochemical device, including a positive electrode plate, which includes the above-mentioned positive electrode material, so that the electrochemical device has good high temperature (45°C and above) cycle stability, kinetic performance (charge and discharge rate), capacity utilization and lower impedance.

[0026] Based on the third aspect, in some possible embodiments, a button battery composed of a positive electrode plate and a lithium plate is charged and discharged within a range of 2.8V to 4.5V at a rate of 0.1C. In the charge and discharge curve of the button battery in the second week, there is a redox peak between 3.5V and 4.0V, and the peak intensity of the redox peak is F1, and F1 is 300mAh / g / V to 900mAh / g / V.

[0027] Based on the third aspect, in some possible embodiments, a button battery composed of a positive electrode plate and a lithium plate is charged and discharged within a range of 2.8V to 4.5V at a rate of 0.1C. In the charge and discharge curve of the button battery in the second week, there is a redox peak between 4.0V and 4.5V, and the peak intensity of the redox peak is F2, and F2 is 300mAh / g / V to 4000mAh / g / V.

[0028] Based on the third aspect, in some possible implementations, the electrochemical device further includes an electrolyte, and the electrolyte includes at least one of 4-fluoro-N,N-dimethylbenzenesulfonamide, 1,4-butanesultone and tert-butyldimethylsilyl glycidyl ether.

[0029] The present invention decomposes HF and PF6 by adding tert-butyl dimethyl silyl glycidyl ether into the electrolyte. - , stabilize the interface between the positive and negative electrodes, and reduce the gas production caused by the parasitic reaction between HF and the residual alkali Li2CO3 on the surface.

[0030] The present application adds 1,4-butane sultone to the electrolyte. Since the highest occupied molecular orbital (HOMO) energy level of 1,4-butane sultone is lower than that of conventional additives, it is similar to carbonates and is also conducive to forming a uniform and stable cathode electrolyte interface film (CEI), thereby further improving the high temperature (45°C and above) cycle stability of the electrochemical device.

[0031] The present application can inhibit the dehydrogenation of ethylene carbonate (EC) by adding 4-fluoro-N,N-dimethylbenzenesulfonamide into the electrolyte, and can also continuously repair the CEI membrane, wherein the CEI membrane is composed of LiF and a benzene ring skeleton with high mechanical strength, and lithium-ion-conducting sulfur-rich and nitrogen-rich lithium-containing substances, further improving the high-temperature (45°C and above) cycle stability performance of the electrochemical device.

[0032] The fourth aspect of the present application provides an electronic device, including the above-mentioned electrochemical device. The electrochemical device has good high-temperature (45°C and above) cycle stability and kinetic performance (charge and discharge rate), while also improving its capacity utilization and reducing its impedance value, which is beneficial to increasing the service life of the electronic device. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the cross-sectional SEM image of the transition metal hydroxide precursor of Example 16. DETAILED DESCRIPTION

[0034] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. The reagents and materials described in the following embodiments can all be obtained from commercial sources.

[0035] Cathode Materials The present application provides a positive electrode material in an embodiment, the positive electrode material includes Li, Na and NO3 - , based on the mass of the cathode material, NO3 - The mass percentage of NO3 is 0.001% to 0.2%. - The mass percentage can be 0.001%, 0.005%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2% or any value within the range consisting of any of the above values.

[0036] This application adds NO3 on the surface of the positive electrode material - , and when its mass proportion is controlled to meet the above range, it is conducive to the formation of a thinner, more uniform and denser solid electrolyte interface film (SEI) on the surface of the positive electrode material, which improves the structural stability of the positive electrode material, so that the electrochemical device of the present application has good high temperature (45°C and above) cycle stability performance. Sodium can occupy the lithium layer to expand the transmission channel of lithium ions, increase the diffusion coefficient of lithium ions in the positive electrode material and the number of lithium ions that can be intercalated and deintercalated. The presence of nitrate ions can form a thinner and denser SEI film on the surface of the positive electrode, increase the diffusion rate of lithium ions on the surface of the positive electrode material, and further improve the kinetic performance (charge and discharge rate) of the electrochemical device.

[0037] Therefore, based on Na and NO3 - The synergistic improvement of the bulk and surface of the positive electrode material greatly improves the high temperature (45°C and above) cycle stability, kinetic performance (charge and discharge rate) and interface impedance of the electrochemical device.

[0038] In some embodiments, the positive electrode material further comprises boron, and the mass proportion of boron is 0.02% to 0.3% based on the mass of the positive electrode material. For example, the mass proportion of boron can be 0.02%, 0.04%, 0.05%, 0.06%, 0.08%, 0.1%, 0.12%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.26%, 0.28%, 0.3% or any value within the range of any of the above values.

[0039] This application forms a dense coating on the surface of the positive electrode material by adding boron elements to the surface of the positive electrode material and controlling its mass ratio to meet the above range, thereby reducing the corrosion of the electrolyte on the surface of the positive electrode material. At the same time, it can reduce the release of oxygen on the surface of the positive electrode material and reduce the phenomenon of irreversible phase change from the surface of the positive electrode material to the bulk phase, thereby further improving the high temperature (45°C and above) cycle stability of the electrochemical device.

[0040] In some embodiments, the particle size Dv50 of the positive electrode material is 2 μm to 15 μm, (Dv90-Dv10) / Dv50 is 0.5 to 1.2, Dv10 is 0.9 μm to 1.9 μm, and Dv90 is 4 μm to 7 μm. For example, Dv50 can be 2 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or any value in the range of any of the above values. For example, (Dv90-Dv10) / Dv50 can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, or any value in the range of any of the above values. For example, Dv10 may be 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or any value in a range consisting of any of the above values. For example, Dv90 may be 4 μm, 4.2 μm, 4.4 μm, 4.6 μm, 4.8 μm, 5 μm, 5.2 μm, 5.4 μm, 5.6 μm, 5.8 μm, 6 μm, 6.2 μm, 6.4 μm, 6.6 μm, 6.8 μm, 7 μm or any value in a range consisting of any of the above values.

[0041] The present application controls the particle size Dv50 of the positive electrode material to meet the above range, which helps to shorten the diffusion path of lithium ions in the positive electrode material and further improves the kinetic performance (charge and discharge rate) of the electrochemical device.

[0042] In addition, the present application also helps to improve the uniform distribution of the positive electrode material particles by controlling (Dv90-Dv10) / Dv10 to meet the above range, which helps to achieve uniform participation of the entire positive electrode material in the electrochemical reaction, thereby improving the capacity utilization of the positive electrode material and improving the overall capacity of the electrochemical device of the present application. Further, the uniform distribution of the positive electrode material particles is also conducive to reducing the uneven phenomenon during the electrochemical reaction, reducing the cracking and detachment of particles caused by stress concentration and volume change, and further improving the high temperature (45°C and above) cycle stability of the electrochemical device, and extending the cycle life of the electrochemical device. Further, the uniform distribution of the positive electrode material particles can further improve the transmission efficiency of lithium ions and reduce the internal resistance, thereby improving the kinetic performance (charge and discharge rate) of the electrochemical device, so that it can maintain a higher capacity at high rate discharge. Further, the uniform distribution of the positive electrode material particles also helps to form a dense and continuous conductive network, reduce the contact resistance between the positive electrode material particles, and thus reduce the impedance of the electrochemical device.

[0043] In some embodiments, the specific surface area BETm of the positive electrode material is 2 / g, 1≤BET≤4. For example, BET can be 1, 1.2, 1.4, 1.6, 1.8, 1.9, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 4 or any value within a range consisting of any of the above values.

[0044] The present application controls the specific surface area of ​​the positive electrode material to meet the above range, which is conducive to providing more interfaces for the insertion and extraction of lithium ions, thereby increasing the capacity of the electrochemical device and further improving the kinetic performance (charge and discharge rate) of the electrochemical device.

[0045] The present application also provides a method for preparing the above-mentioned positive electrode material, comprising the following steps: (1) A metal salt containing Ni, a metal salt containing Mn, and a metal salt containing Co are used as transition metal ion sources, and ammonia water is used as a coprecipitant and a complex, and the three are subjected to a coprecipitation reaction to obtain a transition metal hydroxide precursor; in the present application, the metal salt containing Ni is specifically NiSO4, the metal salt containing Mn is specifically MnSO4, and the metal salt containing Co is specifically CoSO4; (2) sintering a transition metal hydroxide precursor and Na2CO3 in an air atmosphere to obtain an intermediate; (3) treating the intermediate and a lithium-containing compound at 350° C. to 600° C. for 12 to 48 hours, and then washing and drying the intermediate and the lithium-containing compound to obtain a first material; the lithium-containing compound of the present application is specifically lithium hydroxide and lithium nitrate; (4) The first material, sodium nitrate and boron oxide are mixed and then heat treated to obtain the positive electrode material of the present application.

[0046] In the present application, a certain amount of sodium element is added. Since the radius of sodium ions is larger than that of lithium ions, after doping a certain amount of sodium ions in the lithium layer, the interlayer spacing of the lithium layer can be expanded, thereby expanding the channel in the lithium deintercalation process, thereby improving the kinetic performance (charge and discharge rate) and capacity utilization of the electrochemical device. In addition, lattice distortion can be alleviated and the stability of the bulk structure of the positive electrode material can be improved.

[0047] In some embodiments, the transition metal hydroxide precursor has a general formula of Ni a Co c Mn b (OH)2, wherein 0.45≤a≤0.5, 0.45≤b≤0.5, b / a=1, 0≤c≤0.1, a+b+c=1. wherein a can be 0.45, 0.46, 0.47, 0.48, 0.49, 0.5 or any value in the range consisting of any of the above values. b can be 0.45, 0.46, 0.47, 0.48, 0.49, 0.5 or any value in the range consisting of any of the above values. c can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value in the range consisting of any of the above values.

[0048] The above transition metal hydroxide precursor is used to prepare the positive electrode material of the present application, so that the electrochemical device has good high temperature (45°C and above) cycle stability and kinetic performance (charge and discharge rate).

[0049] In some embodiments, the transition metal hydroxide precursor is a spherical secondary particle, the secondary particle includes a first material layer and a second material layer, b / a in the first material layer is 0.83 to 0.94, and b / a in the second material layer is 1 to 1.05; for example, b / a in the first material layer can be 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94 or any value in the range of any of the above values. For example, b / a in the second material layer can be 1, 1.01, 1.02, 1.03, 1.04, 1.05 or any value in the range of any of the above values.

[0050] The first material layer is within a range of 1 / 6R from the center of the secondary particle, the second material layer is other ranges outside the first material layer, and R is the shortest distance from the center of the secondary particle to the surface of the secondary particle.

[0051] In the present application, the atomic weight of the Mn element on the surface of the transition metal hydroxide precursor is controlled to be greater than the atomic weight of the Ni element. Compared with the nickel-rich surface, the manganese-rich surface is more easily reacted with lithium salts, thereby improving the reactivity of the transition metal hydroxide precursor. At the same time, the positive electrode material prepared from the above transition metal hydroxide precursor has better high temperature (45°C and above) cycle stability performance.

[0052] In some embodiments, the specific surface area of ​​the transition metal hydroxide precursor is BETm 2 / g, 9≤BET≤15. For example, BET can be 9, 10, 11, 12, 13, 14, 15 or any value within the range consisting of any of the above values.

[0053] The present application controls the specific surface area of ​​the transition metal hydroxide precursor to meet the above range, so that the transition metal hydroxide precursor has better reaction activity and also has a suitable primary particle size, thereby further improving the high temperature (45°C and above) cycle stability and kinetic performance (charge and discharge rate) of the electrochemical device and reducing the impedance of the electrochemical device.

[0054] In some embodiments, the tap density of the transition metal hydroxide precursor is TD g / cm 3 , 1.7≤TD≤2.2. For example, TD can be 1.7, 1.8, 1.9, 2, 2.1, 2.2 or any value within a range consisting of any of the above values.

[0055] The present application controls the tap density of the transition metal hydroxide precursor to meet the above-mentioned range, so that the transition metal hydroxide precursor has good compactness. The positive electrode material of the present application prepared using this transition metal hydroxide precursor has a suitable specific surface area and compactness, further improving the high temperature (45°C and above) cycle stability and kinetic performance (charge and discharge rate) of the electrochemical device and reducing the impedance of the electrochemical device.

[0056] Positive electrode The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode current collector may be aluminum foil or nickel foil, or may be any composite current collector disclosed in the prior art, for example, including but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate. The positive electrode active material layer includes the positive electrode material of the present application.

[0057] The positive electrode active material layer also includes a binder to bond the positive electrode active material particles to facilitate the formation of a film layer, and at the same time, it can also improve the bonding force between the positive electrode active layer and the positive electrode current collector. In some embodiments, the binder may include but is not limited to polyvinylidene fluoride, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic (ester) styrene butadiene rubber, epoxy resin or nylon, etc. At least one.

[0058] The positive electrode active material layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, conductive carbon black (Super P), acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.

[0059] Negative electrode The negative electrode sheet of the present application includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode current collector may be at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and a polymer substrate. The negative electrode active material layer includes a negative electrode active material, and optionally a conductive agent, a binder and a thickener.

[0060] The specific type of negative electrode material is not subject to specific restrictions and can be selected according to needs. As an example, the negative electrode material includes but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO, lithium-tin alloy, Sn, SnO, SnO2, spinel structured Li4Ti5O 12 , at least one of lithium aluminum alloy.

[0061] The specific type of the binder is not subject to specific restrictions and can be selected according to needs. As an example, the binder includes but is not limited to at least one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), water-based acrylic resin and carboxymethyl cellulose.

[0062] The specific type of thickener is not subject to specific limitation and can be selected according to the requirements. As an example, the thickener includes but is not limited to sodium carboxymethyl cellulose (CMC).

[0063] However, the present application is not limited to the above materials, and the negative electrode plate of the present application may also use other known materials that can be used as negative electrode active materials, conductive agents, binders and thickeners.

[0064] Isolation film The material and shape of the separator used in the electrochemical device of the present application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0065] For example, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be selected.

[0066] A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. The polymer layer contains a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyethylene alkoxy, polyvinylidene fluoride and poly (vinylidene fluoride-hexafluoropropylene).

[0067] Electrolyte According to some embodiments of the present application, the electrolyte includes an organic solvent, a lithium salt, and optional additives.

[0068] In some embodiments, the additive includes at least one of 4-fluoro-N,N-dimethylbenzenesulfonamide, 1,4-butanesultone, and tert-butyldimethylsilyl glycidyl ether.

[0069] The present invention decomposes HF and PF6 by adding tert-butyl dimethyl silyl glycidyl ether into the electrolyte. - , stabilize the interface between the positive and negative electrodes, and reduce the gas production caused by the parasitic reaction between HF and the residual alkali Li2CO3 on the surface.

[0070] The present application adds 1,4-butane sultone to the electrolyte. Since the highest occupied molecular orbital (HOMO) energy level of 1,4-butane sultone is lower than that of conventional additives, it is similar to carbonates and is also conducive to forming a uniform and stable cathode electrolyte interface film (CEI), thereby further improving the high temperature (45°C and above) cycle stability of the electrochemical device.

[0071] The present application can inhibit the dehydrogenation of ethylene carbonate (EC) by adding 4-fluoro-N,N-dimethylbenzenesulfonamide into the electrolyte, and can also continuously repair the CEI membrane, wherein the CEI membrane is composed of LiF and a benzene ring skeleton with high mechanical strength, and lithium-ion-conducting sulfur-rich and nitrogen-rich lithium-containing substances, further improving the high-temperature (45°C and above) cycle stability performance of the electrochemical device.

[0072] In some embodiments, the lithium salt includes, but is not limited to, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalatoborate) LiB(C2O4)2 (LiBOB), or lithium di(difluorooxalatoborate) LiBF2(C2O4) (LiDFOB).

[0073] In some embodiments, the organic solvent includes, but is not limited to, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate, or ethyl propionate.

[0074] Electrochemical Devices The electrochemical device of the present application also includes a shell (such as a packaging bag) for accommodating the above-mentioned positive electrode sheet, separator, negative electrode sheet and electrolyte, as well as other components known in the electrochemical field. The present application does not limit the above-mentioned other components. The present application has no special restrictions on the shell, which can be a shell known in the art, as long as the purpose of the present application can be achieved. For example, an aluminum-plastic film packaging bag can be used. The present application does not specifically limit the type of chemical device, which can include any device in which an electrochemical reaction occurs. The electrochemical device containing the above-mentioned positive electrode material has good high temperature (45°C and above) cycle stability, kinetic performance (charge and discharge rate), capacity utilization and low impedance.

[0075] Electronic Devices The electrochemical device is applied to an electronic device to power the load in the electronic device. Moreover, the electrochemical device has good high temperature (45°C and above) cycle stability, kinetic performance (charge and discharge rate), capacity utilization and low impedance, which is conducive to improving the service life of the electronic device. Among them, the electronic device may include but is not limited to laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.

[0076] Example 1 <Preparation of positive electrode material> 1. Prepare 2mol / L NiSO4, 1.78mol / L MnSO4, 2.04mol / L MnSO4 and 5mol / L NH4OH solution and sodium hydroxide capacity. The first stage: first, introduce 2mol / L NiSO4 and 1.78mol MnSO4 solution into the reactor at equal flow rates. The stirring rate of the reactor is 1000r / min, the constant temperature in the reactor is 50°C, and N2 protective gas is continuously introduced to reduce the oxidation of transition metal ions. At the same time, introduce 5mol / L NH4OH solution at a certain flow rate, keep the molar ratio of NH4OH / TM (TM is the sum of transition metal ions) at 1.2, and introduce sodium hydroxide solution to keep the pH of the reaction solution at about 12. The second stage: After a period of reaction, replace the 1.78mol / L MnSO4 solution with a 2.04mol / L MnSO4 solution. After sufficient precipitation, the transition metal hydroxide precursor of the present application can be obtained.

[0077] 2. Fully mix the transition metal hydroxide precursor and Na2CO3 (molar ratio Na:TM=1.05:1), heat to 900℃ in an air atmosphere at a heating rate of 10℃ / min, then keep the temperature at 900℃ for 24h, and then quickly cool to room temperature at a cooling rate of 50℃ / min. The atmosphere during the cooling stage is N2, and the intermediate can be obtained.

[0078] 3. After mixing the intermediate, LiOH.H2O and LiNO3 (the molar ratio of LiOH.H2O to LiNO3 is 1:1, and the molar ratio of Li / TM is 20), heat to 500°C at 10°C / min in a nitrogen atmosphere, then keep the temperature at 500°C for 24 hours, and finally cool to room temperature at a cooling rate of 20°C / min. The cooled product is fully washed with deionized water and filtered, and the filter cake is vacuum dried at 100°C for 24 hours. After sieving, the first material can be obtained.

[0079] 4. Thoroughly mix the above-mentioned first material with a certain amount of sodium nitrate, heat it to 500°C at a heating rate of 10°C / min in a nitrogen atmosphere, keep it at 500°C for 12 hours, then cool it to room temperature at a cooling rate of 10°C / min, and sieve to obtain the positive electrode material of the present application.

[0080] <Preparation of positive electrode sheet> The binder polyvinylidene fluoride (PVDF), the conductive agent conductive carbon black (Super P), and the positive electrode material are mixed uniformly in a weight ratio of 1.5:1.5:97, and N-methylpyrrolidone (NMP) is added as a solvent to obtain a positive electrode slurry, wherein the viscosity of the positive electrode slurry is 3000 mPas to 6000 mPas; the positive electrode slurry is uniformly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10 μm, and dried at 120°C for 1 hour to obtain a positive electrode sheet coated with a positive electrode material layer with a thickness of 60 μm on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Dry under vacuum conditions at 120°C for 1 hour, and then cold press, cut pieces, and weld the pole ears to obtain a positive electrode sheet with a specification of 38mm×58mm.

[0081] <Preparation of negative electrode sheet> After mixing the negative electrode material graphite, thickener sodium carboxymethyl cellulose (CMC-Na), and binder styrene-butadiene rubber (SBR) in a weight ratio of 96:2:2, deionized water was added, and the mixture was stirred to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry was 75wt%; the negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12μm, and dried at 120°C to obtain a negative electrode sheet with a coating thickness of 80μm and a single-sided negative electrode material layer. Repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided negative electrode material layer. Dry under vacuum conditions at 120°C for 1 hour, and then obtain a negative electrode sheet with a specification of 40mm×60mm after cold pressing, cutting, and slitting.

[0082] <Preparation of Electrolyte> In an argon atmosphere glove box with a water content of <10ppm, propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) were mixed in a mass ratio of 1:1:1, and then fully dried lithium salt LiPF6 was dissolved in the above non-aqueous solvent to prepare the electrolyte in the embodiment. Based on the mass of the electrolyte, the mass proportion of LiPF6 is 13%.

[0083] <Preparation of Separator Film> A polyethylene (PE) porous polymer film with a thickness of 7 μm was used as the isolation membrane.

[0084] <Preparation of lithium-ion soft-pack batteries> The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound. After welding the pole ear, the electrode assembly is placed in an aluminum-plastic film packaging bag, and the electrolyte is injected after drying. After vacuum packaging, standing, forming (forming upper limit voltage is 4.35V, forming temperature is 85℃, and forming standing time is 2 hours), degassing, trimming and other processes, a lithium-ion soft-pack battery is obtained.

[0085] <Preparation of lithium-ion button cells> The single-sided coated positive electrode sheet was cut into Φ (diameter) = 14 mm discs as the working electrode, and a Φ (diameter) = 18 mm metal lithium sheet was used as the reference electrode. The two were separated by a Φ (diameter) = 20 mm isolation membrane, and an appropriate amount of electrolyte was added to assemble a CR2430 button-type lithium-ion battery.

[0086] Examples 2 and 3 The difference between Examples 2 and 3 and Example 1 is that in the first and second stages of step 1 of <Preparation of Positive Electrode Materials>, in addition to passing NiSO4 and MnSO4 solutions, CoSO4 solution is also passed, and the remaining conditions / preparation methods are the same as those of Example 1. The above-mentioned specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0087] Examples 4 and 5 The difference between Examples 4 and 5 and Example 1 is that in step 4 of <Preparation of Positive Electrode Material>, the amount of sodium nitrate added is different, and the other conditions / preparation methods are the same as those of Example 1. The above specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0088] Examples 6 to 9 The difference between Examples 6 to 9 and Example 1 is that in step 1 of <Preparation of Positive Electrode Materials>, the concentrations of the first-stage and second-stage MnSO4 solutions are adjusted respectively, and the remaining conditions / preparation methods are the same as those in Example 1. The above-mentioned specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0089] Examples 10 and 11 The difference between Examples 10 and 11 and Example 1 is that in step 4 of <Preparation of Positive Electrode Material>, boron oxide is added in different amounts, and the other conditions / preparation methods are the same as those of Example 1. The above specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0090] Examples 12 to 14 The difference between Examples 12 to 14 and Example 1 is that in step 1 of <Preparation of Positive Electrode Material>, the introduction rate of the first stage and the second stage transition metal sulfate solution is adjusted, and the other conditions / preparation methods are the same as those in Example 1. The above specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0091] Examples 15 to 20 The difference between Examples 15 to 20 and Example 1 is that in step 1 of <Preparation of Positive Electrode Materials>, the reaction time of the first stage and the second stage is regulated, and the other conditions / preparation methods are the same as those of Example 1. The above-mentioned specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0092] Implementation of 21 and 22 The difference between Examples 21 and 22 and Example 1 is that in step 1 of <Preparation of Positive Electrode Material>, the reaction time of the second stage is regulated, and the other conditions / preparation methods are the same as those of Example 1. The above specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0093] Embodiment 23 The difference between Example 23 and Example 1 is that, in <Preparation of Electrolyte>, 3% 4-fluoro-N,N-dimethylbenzenesulfonamide, 3% 1,4-butanesulfonate and 3% tert-butyldimethylsilyl glycidyl ether are added, and the remaining conditions / preparation methods are the same as those in Example 1. The above specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0094] Examples 24 to 26 The difference between Examples 24 to 26 and Example 1 is that in <Preparation of Electrolyte>, 1% of 4-fluoro-N,N-dimethylbenzenesulfonamide, 3% of 4-fluoro-N,N-dimethylbenzenesulfonamide, and 5% of 4-fluoro-N,N-dimethylbenzenesulfonamide are added respectively, and the other conditions / preparation methods are the same as those in Example 1. The above specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0095] Examples 27 to 29 The difference between Examples 27 to 29 and Example 1 is that in <Preparation of Electrolyte>, 1% 1,4-butane sultone, 3% 1,4-butane sultone, and 5% 1,4-butane sultone are added respectively, and the other conditions / preparation methods are the same as those in Example 1. The above specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0096] Examples 30 to 32 The difference between Examples 30 to 32 and Example 1 is that, in <Preparation of Electrolyte>, 1% of tert-butyldimethylsilyl glycidyl ether, 3% of tert-butyldimethylsilyl glycidyl ether, and 5% of tert-butyldimethylsilyl glycidyl ether are added respectively, and the other conditions / preparation methods are the same as those in Example 1. The above specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0097] Comparative Examples 1 and 2 The difference between Comparative Examples 1 and 2 and Example 1 is that in step 4 of <Preparation of Positive Electrode Material>, the amount of NaNO3 added is different, and the other conditions / preparation methods are the same as those in Example 1. The above specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0098] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in step 4 of <Preparation of positive electrode material>, NaNO3 is not added, and the prepared positive electrode material does not contain NO3 - , the other conditions / preparation methods are the same as those in Example 1, and the above specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0099] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that in step 4 of <Preparation of Positive Electrode Material>, sodium nitrate is replaced by lithium nitrate, and the prepared positive electrode material does not contain sodium element, and the other conditions / preparation method are the same as those in Example 1, and the above-mentioned specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0100] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that in the preparation of positive electrode material, step 4 is omitted, and the prepared positive electrode material does not contain sodium and NO3. - , the other conditions / preparation methods are the same as those in Example 1, and the above specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0101] Test Method (1) Atomic weight test of each element in transition metal hydroxide precursor Use aqua regia solution to dissolve the transition metal hydroxide precursor (for example, 0.4g of transition metal hydroxide precursor uses 10ml of aqua regia solution (aqua regia solution is a 1:1 volume ratio of aqua regia to deionized water, and aqua regia is a 3:1 volume ratio of concentrated hydrochloric acid to concentrated nitric acid), dilute to 100mL, and then use an ICP analyzer to test the mass percentage of elements such as Ni, Co and Mn in the solution (such as m(Ni), m(Co), m(Mn)). Assuming that the mass of the precursor is 100g, the method for calculating the atomic weight based on the mass percentage of each element is: m(Ni) = mass percentage of nickel element / relative atomic mass of nickel = m(Ni) / 58.693 (mol). Similarly, the atomic weight of other elements can be calculated.

[0102] (2) Atomic weight (b / a) test of each element in the first material layer and the second material layer Transition metal hydroxide precursor cross section (CP) sample preparation and pretreatment method: 1) Clean the glass slide and Teflon-coated glass for sample preparation, squeeze out a drop of Hardener-G2 and 10 drops of Resin-G2 and mix them evenly with a toothpick, then add cathode powder and mix evenly until the viscosity reaches the sample preparation requirement; 2) Transfer the stirred sample to a glass slide with Teflon in a certain size, clamp the two glass slides and place them on the heater to heat (100-110) until completely solidified; 3) Grind the solidified disc with sandpaper to make a flat interface, and then perform CP cutting. CP cutting is performed in a vacuum environment and polished with argon ions; 4) Take out the cut sample, place it on the SEM dedicated sample stage, and then put it into the SEM instrument for testing.

[0103] EDS test of transition metal hydroxide precursor CP: Use the energy dispersive X-ray spectrometer (EDS) built into the scanning electron microscope (instrument model: ThermoScientific FEI-Apreo S SEM, acceleration voltage: 0.2KV to 30KV) to perform EDS point scanning or small area surface scanning on the area within 1 / 6R of the cross section of the transition metal hydroxide precursor, and the atomic weight (b / a) of each element in the first material layer can be obtained. Similarly, use EDS to perform EDS point scanning or small area surface scanning on the area outside 1 / 6R of the cross section of the transition metal hydroxide precursor to obtain the atomic weight (b / a) of each element in the second material layer.

[0104] Among them, regarding the measurement of R: if the transition metal hydroxide precursor is a single secondary particle, R is the shortest distance from the center of the secondary particle to the surface of the secondary particle; if the transition metal hydroxide precursor is a secondary particle formed by agglomeration of two or more particles, R is still measured by dividing it into single secondary particles.

[0105] (3) Specific surface area test method In accordance with the national standard "Determination of the specific surface area of ​​solid substances by gas adsorption BET method" (GB / T 19587-2017), the specific surface area analyzer (model TristarⅡ3020) was used to test the specific surface area of ​​the positive electrode material and transition metal hydroxide precursor by nitrogen adsorption method.

[0106] (4) Tap density TD test of transition metal hydroxide precursors In accordance with the national standard GB / T 24533-2019, a density analyzer (model: GeoPyc 1365) was used to test the tap density TD of the transition metal hydroxide precursor.

[0107] (5) Test of element content in positive electrode materials Use aqua regia solution to dissolve the positive electrode material powder (for example, 0.4 g of positive electrode material powder uses 10 ml of aqua regia solution (aqua regia solution is aqua regia to deionized water in a volume ratio of 1:1, and aqua regia is concentrated hydrochloric acid to concentrated nitric acid in a volume ratio of 3:1), dilute to 100 mL, and then use an ICP analyzer to test the mass percentage of elements such as Ni, Co and Mn in the solution.

[0108] (6) Particle size test method The positive electrode material is dispersed in anhydrous ethanol for particle size distribution measurement. The particle size analysis instrument model is MasterSizer3000, and the particle sizes Dv10, Dv50 and Dv90 of the positive electrode material are obtained. Among them, Dv10, Dv50 and Dv90 represent the cumulative values ​​under the particle size volume distribution, indicating that the particles smaller than the particle size value in the sample account for 10%, 50% and 90% of the total volume of the total sample.

[0109] (7) 45℃ cycle capacity retention test Place the lithium-ion soft-pack battery in a 45℃ constant temperature box and let it stand for 30 minutes to make the lithium-ion soft-pack battery reach a constant temperature; charge the lithium-ion soft-pack battery that has reached a constant temperature to 4.35V at 1.5C constant current at 45℃, and then charge it to 0.02C at 4.35V; let it stand for 5 minutes, and then discharge it to 2.8V at 4C constant current, let it stand for 5 minutes, and test the discharge capacity of this time as the first cycle discharge capacity; charge and discharge the battery 300 times in this way, and the discharge capacity of the 300th cycle of the test battery is recorded as the 300th cycle discharge capacity. The capacity retention rate (%) of the lithium-ion soft-pack battery cycled 300 times at 45℃ = 300th cycle discharge capacity / first cycle discharge capacity × 100%.

[0110] (8) 2C / 0.1C test method The lithium-ion soft-pack battery is charged to 4.35V at 0.7C at 25°C, and then charged to 0.025C at 4.35V; let it stand for 5 minutes, and then discharged to 2.8V at 0.1C; let it stand for 5 minutes. Charge to 4.35V at 0.7C, and then charge to 0.025C at 4.35V; let it stand for 5 minutes, and then discharge to 2.8V at 2C; let it stand for 5 minutes. The ratio of the above 2C constant current discharge capacity divided by the 0.1C constant current discharge capacity is the rate 2C / 0.1C.

[0111] (9) dQ / dV test of the first week charge capacity, the first week discharge capacity and the second week charge and discharge First-week charge capacity and first-week discharge capacity test: The lithium-ion button cell was charged and discharged at 25°C using a blue-power device. The charging parameters are: first charge to 4.5V with a current density of 20 mA / g, then charge at a constant voltage at a voltage of 4.5V until the current is less than 50 uA, and then stand for 5 min. The discharge parameters are: discharge at a current density of 20 mA / g until the voltage is less than 2.8 V, and then stand for 5 min. For the button cell that has just been installed, charge it first and then discharge it, and then repeat the charge and discharge in sequence. The capacity obtained by charging in the first week is divided by the active mass of the positive electrode to obtain the first-week charge capacity. Similarly, the capacity obtained by discharging in the first week is divided by the active mass of the positive electrode to obtain the first-week discharge capacity. dQ / dV test of charging and discharging in the second week: The specific capacity-voltage curve of the above button cell in the second week of charging and discharging, the corresponding dq / dV curve can be obtained by differentiating the specific capacity against the voltage.

[0112] (10) Impedance test at 25°C The impedance test of lithium-ion battery soft pack was carried out using an electrochemical workstation (Solartron 1470E / 1455 electrochemical workstation, UK). The test environment temperature was 25°C, the frequency range of the electrochemical workstation was 0.03 Hz-50KHz, and the lithium-ion soft pack battery was discharged to 2.8 V at a current density of 100 mA / g before the impedance test. The real impedance value corresponding to the intersection of the charge transfer impedance end and the diffusion impedance of the Nyquist diagram is the impedance of the lithium-ion soft pack battery.

[0113] Figure 1 This is a cross-sectional SEM image of the transition metal hydroxide precursor of Example 16. It can be seen from the image that two or more secondary particles of the transition metal hydroxide precursor may be stuck together.

[0114] The test data of Examples 1 to 32 and Comparative Examples 1 to 5 are recorded in Tables 1 to 3.

[0115] Table 1 Note: “ / ” in Table 1 means there is no corresponding substance or parameter.

[0116] Table 2 Note: “ / ” in Table 2 means there is no corresponding substance or parameter Table 3 It can be seen from Tables 1 to 3 that compared with Example 1, Examples 2 and 3 adjust the atomic weight of the Mn element, the atomic weight of the Ni element and the atomic weight of the Co element in the transition metal hydroxide precursor. When the atomic weights of the three meet the scope of this application, the electrochemical device has good high temperature (45°C and above) cycle stability, kinetic performance (charge and discharge rate) and low impedance, as well as relatively good capacity utilization.

[0117] Compared with Example 1, Examples 4 and 5 adjust the amount of sodium nitrate added in step 3 of <Preparation of positive electrode material>, and NO3 - The mass proportion (0.001% to 0.2%) meets the scope of this application, so that the electrochemical device has good high temperature (45°C and above) cycle stability, kinetic performance (charge and discharge rate) and low impedance, while also having relatively good capacity utilization.

[0118] Compared with Example 1, Examples 6 to 9 meet the scope of the present application by adjusting the b / a (0.83 to 0.94) of the first material layer and the b / a (1 to 1.05) of the second material layer in the transition metal hydroxide precursor, so that the electrochemical device has good high temperature (45°C and above) cycle stability, kinetic performance (charge and discharge rate) and low impedance, while also having relatively good capacity utilization.

[0119] Compared with Example 1, Examples 10 to 11 add a certain amount of boron oxide in step 3 of <Preparation of positive electrode material> and adjust the BET (1m 2 / g to 4m 2 / g) meets the scope of this application, so that the electrochemical device has better high temperature (45°C and above) cycle stability performance.

[0120] Compared with Example 1, Examples 12 to 14 adjust the BET (9m 2 / g to 15m 2 / g) meets the scope of this application, so that the electrochemical device has better kinetic performance (charge and discharge rate).

[0121] Compared with Example 1, Examples 15 to 18 adjust the particle size Dv50 (2μm to 15μm) of the positive electrode material to make the electrochemical device have better kinetic performance (charge and discharge rate); Examples 19 and 20 adjust (Dv90-Dv10) / Dv50 (0.5 to 1.2) to meet the scope of this application, so that the electrochemical device has good high temperature (45°C and above) cycle stability, kinetic performance (charge and discharge rate) and low impedance, while also having relatively good capacity utilization.

[0122] Compared with Example 1, Examples 21 to 22 adjust the tap density TD of the transition metal hydroxide precursor (1.7 g / cm 3 Up to 2.2 g / cm 3 ) meets the scope of this application, so that the electrochemical device has a lower impedance.

[0123] Compared with Example 1, Examples 23 to 32 further improve the high temperature (45°C and above) cycle stability and kinetic performance (charge and discharge rate) of the electrochemical device by adding different mass contents of 4-fluoro-N,N-dimethylbenzenesulfonamide, 1,4-butanesulfonate and tert-butyldimethylsilyl glycidyl ether in <Preparation of electrolyte>, and also reduce the impedance of the electrochemical device.

[0124] Compared with Comparative Examples 1 and 2, Example 1 controls the amount of NO3 in the positive electrode material by adjusting the amount of NaNO3 added in step 3 of <Preparation of positive electrode material>. - When the mass proportion of meets the range of 0.001% to 0.2% in this application, the high temperature (45°C and above) cycle stability of the electrochemical device is significantly improved. In Comparative Example 3, NaNO3 is not added in step 3 of <Preparation of positive electrode material>. It can be seen that compared with Comparative Example 3, Example 1 further improves the high temperature (45°C and above) cycle stability of the electrochemical device. It can be seen that NO3 in the positive electrode material - The mass ratio of NO3 in the positive electrode material will affect the stability of the electrochemical device. - When the mass proportion meets the scope of this application, the electrochemical device has better high temperature (45°C and above) cycle stability performance.

[0125] In step 4 of <Preparation of Positive Electrode Material> of Comparative Example 4, sodium nitrate is replaced with lithium nitrate. It can be seen that compared with Comparative Example 4, Example 1 further improves the high temperature (45°C and above) cycle stability and kinetic performance (charge and discharge rate) of the electrochemical device and reduces the impedance, while also having a relatively good capacity utilization.

[0126] In the <Preparation of Positive Electrode Materials> of Comparative Example 5, step 4 is not included. It can be seen that compared with Comparative Example 5, Example 1 further improves the high temperature (45°C and above) cycle stability and kinetic performance (charge and discharge rate) of the electrochemical device and reduces the impedance, while also having a relatively good capacity utilization.

[0127] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application is described in detail with reference to the above implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A positive electrode material, characterized in that: The positive electrode material includes lithium element, sodium element and nitrate ions. Based on the mass of the positive electrode material, the mass proportion of the nitrate ions is 0.001% to 0.2%.

2. The positive electrode material according to claim 1, characterized in that The positive electrode material also includes a boron element, and based on the mass of the positive electrode material, the mass proportion of the boron element is 0.02% to 0.3%.

3. The positive electrode material according to claim 1, characterized in that The particle size Dv50 of the positive electrode material is 2 μm to 15 μm, and (Dv90-Dv10) / Dv50 is 0.5 to 1.

2.

4. The positive electrode material according to claim 1, characterized in that The particle size Dv50 of the positive electrode material is 3.3 μm to 10 μm, and (Dv90-Dv10) / Dv50 is 0.7 to 0.

9.

5. The positive electrode material according to any one of claims 1 to 4, characterized in that: The specific surface area BETm of the positive electrode material 2 / g, 1≤BET≤4.

6. A method for preparing a positive electrode material according to any one of claims 1 to 5, characterized in that: include: A metal salt containing a nickel element, a metal salt containing a manganese element, a metal salt containing a cobalt element, sodium hydroxide and ammonia water are subjected to a coprecipitation reaction to obtain a transition metal hydroxide precursor; sintering the transition metal hydroxide precursor and sodium carbonate in an air atmosphere to obtain an intermediate; Treating the intermediate with a lithium-containing compound at 350° C. to 600° C. for 12 to 48 hours, then washing and drying, to obtain a first material; The first material, sodium nitrate and boron oxide are mixed and then heat treated to obtain the positive electrode material.

7. The preparation method according to claim 6, characterized in that: The chemical formula of the transition metal hydroxide precursor is Ni a Co c Mn b (OH)2, where 0.45≤a≤0.5, 0.45≤b≤0.5, b / a=1, 0≤c≤0.1, a+b+c=1.

8. The preparation method according to claim 7, characterized in that: The transition metal hydroxide precursor is a spherical secondary particle, the secondary particle comprises a first material layer and a second material layer, b / a in the first material layer is 0.83 to 0.94, and b / a in the second material layer is 1 to 1.05; The first material layer is within a range of 1 / 6R from the center of the secondary particle, where R is the distance from the center of the secondary particle to the surface of the secondary particle.

9. The preparation method according to claim 6, characterized in that: The specific surface area BETm of the transition metal hydroxide precursor 2 / g, 9≤BET≤15.

10. The preparation method according to claim 6, characterized in that: The tap density of the transition metal hydroxide precursor is TDg / cm 3 , 1.7≤TD≤2.

2.

11. An electrochemical device comprising a positive electrode plate, characterized in that: The positive electrode sheet comprises the positive electrode material according to any one of claims 1 to 5.

12. The electrochemical device according to claim 11, characterized in that A charge and discharge test is performed on a button-type battery composed of the positive electrode sheet and the lithium sheet within a range of 2.8V to 4.5V at a rate of 0.1C. The charge and discharge curve of the button-type battery in the second week satisfies at least one of the following characteristics: (1) The button battery has a redox peak between 3.5V and 4.0V, the peak intensity of the redox peak is F1, and F1 is 300mAh / g / V to 900mAh / g / V; (2) The button cell has a redox peak between 4.0 V and 4.5 V, the peak intensity of the redox peak is F2, and F2 is 300 mAh / g / V to 4000 mAh / g / V.

13. The electrochemical device according to claim 11, characterized in that The electrochemical device further includes an electrolyte, wherein the electrolyte includes at least one of 4-fluoro-N,N-dimethylbenzenesulfonamide, 1,4-butane sultone, and tert-butyldimethylsilyl glycidyl ether.

14. An electronic device, characterized in that: Comprising the electrochemical device according to any one of claims 11 to 13.

Citation Information

Patent Citations

  • Secondary battery and electric device

    CN117638198A

  • Electrolyte solution for secondary battery, secondary battery, battery module, battery pack, and electric device

    CN118352628A

  • Positive electrode material, electrochemical device, and electronic device

    CN118743053A

  • Polymer film carrying electrolyte and secondary battery using the same

    JP2001118559A

  • Nickel manganese composite hydroxide particle and production method thereof, positive electrode active material for nonaqueous electrolyte secondary battery and production method thereof, and nonaqueous electrolyte secondary battery

    JP2012256435A